KINERJA RESEPSIONIS DALAM MEMBERIKAN PELAYANAN PRIMA PADA PT JIAEC DEPOK - Yoeliastuti Yoeliastuti; Mirayana Trie Cahyani (JURNAL LENTERA BISNIS, 2021)
This study aims to determine the performance of the receptionist in providing excellent service at PT JIAEC Depok, as well as to find out the obstacles faced and the solutions made in overcoming the obstacles faced. The receptionist's performance in providing excellent service includes receiving guests, handling incoming and outgoing calls, receiving and inputting goods or documents, delivering announcements and filing airwaybill documents to Japan. The obstacles faced in receiving guests are the inability of the receptionist to speak Japanese, poor signal when receiving incoming calls, no confirmation when receiving documents. The solutions to the existing obstacles are; looking for help from employees who can speak Japanese, telling the caller to look for a place with good signal, the receptionist routinely checks in the virtual office for documents that have not been confirmed. This research is a qualitative descriptive research conducted by searching for literature and references through literature study, observation and interviews.Keywords: Performance, Receptionist, Excellent Service